Human parasites in the Roman World: health consequences of conquering an empire. Issue 1 (8th January 2016) - MITCHELL, PIERS D.
SUMMARY: The archaeological evidence for parasites in the Roman era is presented in order to demonstrate the species present at that time, and highlight the health consequences for people living under Roman rule. Despite their large multi-seat public latrines with washing facilities, sewer systems, sanitation legislation, fountains and piped drinking water from aqueducts, we see the widespread presence of whipworm ( Trichuris trichiura ), roundworm ( Ascaris lumbricoides ) and Entamoeba histolytica that causes dysentery. This would suggest that the public sanitation measures were insufficient to protect the population from parasites spread by fecal contamination. Ectoparasites such as fleas, head lice, body lice, pubic lice and bed bugs were also present, and delousing combs have been found. The evidence fails to demonstrate that the Roman culture of regular bathing in the public baths reduced the prevalence of these parasites. Fish tapeworm was noted to be widely present, and was more common than in Bronze and Iron Age Europe. It is possible that the Roman enthusiasm for fermented, uncooked fish sauce (garum) may have facilitated the spread of this helminth. Roman medical practitioners such as Galen were aware of intestinal worms, explaining their existence and planning treatment using the humoural theory of the period.